Microfibrillar-associated protein 5 regulates osteogenic differentiation by modulating the Wnt/β-catenin and AMPK signaling pathways - Haoran Li; Wuling Zhou; Shiwei Sun; Tianlong Zhang; Tieqi Zhang; Haitian Huang; Minghai Wang (BMC, 2021)
Abstract Background Dysfunctional osteogenesis of bone marrow mesenchymal stem cells (BMSCs) plays an important role in osteoporosis occurrence and development. However, the molecular mechanisms of osteogenic differentiation remain unclear. This study explored whether microfibrillar-associated protein 5 (MFAP5) regulated BMSCs osteogenic differentiation. Methods We used shRNA or cDNA to knock down or overexpress MFAP5 in C3H10 and MC3T3-E1 cells. AR-S- and ALP-staining were performed to quantify cellular osteogenic differentiation. The mRNA levels of the classical osteogenic differentiation biomarkers Runx2, Col1α1, and OCN were quantified by qRT-PCR. Finally, we employed Western blotting to measure the levels of Wnt/β-catenin and AMPK signaling proteins. Results At days 0, 3, 7, and 14 after osteogenic induction, AR-S- and ALP-staining was lighter in MFAP5 knockdown compared to control cells, as were the levels of Runx2, Col1α1 and OCN. During osteogenesis, the levels of β-catenin, p-GSK-3β, AMPK, and p-AMPK were upregulated, while that of GSK-3β was downregulated, indicating that Wnt/β-catenin and AMPK signaling were activated. The relevant molecules were expressed at lower levels in the knockdown than control group; the opposite was seen for overexpressing cell lines. Conclusions MFAP5 regulates osteogenesis via Wnt/β‑catenin- and AMPK-signaling; MFAP5 may serve as a therapeutic target in patients with osteoporosis.